2020
DOI: 10.1186/s12870-020-02644-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification, characterization and functional analysis of AGAMOUS subfamily genes associated with floral organs and seed development in Marigold (Tagetes erecta)

Abstract: Background AGAMOUS (AG) subfamily genes regulate the floral organs initiation and development, fruit and seed development. At present, there has been insufficient study of the function of AG subfamily genes in Asteraceae. Marigold (Tagetes erecta) belongs to Asteraceae family whose unique inflorescence structure makes it an important research target for understanding floral organ development in plants. Results Four AG subfamily genes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…The phylogenetic analysis showed that MADS-box family members could be divided into two main types and 15 subfamilies according to the established model for plant classification [ 21 ]. In terms of gene structure and protein conserved motifs, the conservation within the same family was significant, but there were large structural differences among different families as found in marigold [ 45 ] and bamboo [ 41 ]. In the process of higher plant evolution, the conservation and number of introns in the plant type I MADS-box family were relatively low, while type II MADS-box family members with the K-box structure were more conservative and richer in introns, similar to wheat and orchid MADS-box genes [ 5 , 6 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phylogenetic analysis showed that MADS-box family members could be divided into two main types and 15 subfamilies according to the established model for plant classification [ 21 ]. In terms of gene structure and protein conserved motifs, the conservation within the same family was significant, but there were large structural differences among different families as found in marigold [ 45 ] and bamboo [ 41 ]. In the process of higher plant evolution, the conservation and number of introns in the plant type I MADS-box family were relatively low, while type II MADS-box family members with the K-box structure were more conservative and richer in introns, similar to wheat and orchid MADS-box genes [ 5 , 6 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that MADS-box genes belonging to the type I clade are mainly involved in the development of the female gametophyte, the embryo, and seeds, while plant type II MADS-box genes have specific roles in flower organ development, especially in specifying floral organ identity [ 39 , 48 ]. In most plants, different subfamily members often have different expression patterns [ 45 , 49 ]. In our study, the transcript abundance in the flower development of type I clade genes was extremely low, while the subfamilies belonging to the type II clade displayed diverse expression patterns, and most of the type II genes were expressed in the reproductive organs, thereby indicating that type II MADS genes might play important roles in flower development in safflower.…”
Section: Discussionmentioning
confidence: 99%
“…The primers were presented in Supplementary Table S1 . The bait and prey constructs of five class B genes ( TeAP3-1 , TeAP3-2 , TePI , TeTM6-1 , and TeTM6-2 ) and class C + D genes (C: TeAG1 and TeAG2 , D: TeAGL11-1 and TeAGL11-2 ) were previously described by Ai et al [ 49 ] and Zhang et al [ 50 ], respectively. The full-length sequences of six class E genes ( TeSEP1 , TeSEP3-1 , TeSEP3-2 , TeSEP3-3 , TeSEP4 and TeAGL6 ) were downloaded from NCBI, and bait and prey recombinants of these six class E genes were also constructed, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…These characteristics make marigold a valuable material for studying the molecular mechanism of marigold inflorescence formation. In our previous work, we have obtained functionally characterized class B (TePI, TeAP3-1, TeAP3-2, TeTM6-1, and TeTM6-2) [ 49 ], C (TeAG1 and TeAG2) [ 50 ], D (TeAGL11-1 and TeAGL11-2) [ 50 ], and E (TeSEP1, TeSEP3-1, TeSEP3-2, TeSEP3-3, and TeSEP4) [ 51 ] genes, which are active during marigold inflorescence and floret development and have specific expression patterns in floral organs. In this study, we cloned and characterized five AP1/FUL -like genes in marigold, whose distinct expression patterns, protein interaction patterns, and different phenotypes in Arabidopsis transgenic lines might imply divergent functions of these five genes in regulating the floral meristem development, floral organ identity, and flowering time.…”
Section: Introductionmentioning
confidence: 99%
“…The African marigold (Tagetes erecta) is an annual plant in the Marigold genus of the Asteraceae family (Panwar et al, 2013;Zhang et al, 2020). It is a plant native to Mexico and South America (Sreekala and Raghava, 2003;Cicevan et al, 2015) and is commonly cultivated as an ornamental plant worldwide (Vasudevan, et al, 1997;Panwar et al, 2013;Cicevan et al, 2022).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%